Proceso de intención de enfermería en paciente femenino de 60 años de edad con diagnóstico de taquicardia paroxística. - Fajardo Estévez, José María (2024)
Paroxysmal tachycardia is a disease that consists of a rapid and uniform heart rate (160-222 beats per minute). This pathology begins and disappears suddenly and has its origin in cardiac tissues other than the ventricles. Usually and in most cases, the person affected by this disease notices a strong and rapid heartbeat, dyspnea and pain in the chest. In this case study, all nursing interventions have been implemented, which has allowed the patient to show significant progress in her recovery. Furthermore, each and every one of the objectives set has been met, thus allowing their fulfillment to be achieved, facilitating their improvement. Furthermore, it is important to indicate that the patient received each and every one of the nursing care that allowed her an optimal recovery and improvement in her state of health. It should be noted that in this study we can know what the main symptoms were that led us to be able to implement nursing actions. In conclusion, but no less significant, it is important to highlight that this case study, focused on a patient with paroxysmal tachycardia, contributed greatly to her recovery and provided valuable knowledge in the field of care.